Peran Literasi Keuangan dan E-Wallet dalam Mendorong Keputusan Investasi Generasi Z di Era Keuangan Digital - Asbaruna, Latifah Wulandari (Jurnal Dimamu, 2025)
The rapid growth of financial technology has transformed how young generations manage and interact with their finances, particularly in investment decision-making. This study aims to analyze the role of financial literacy and e-wallet usage in encouraging investment decisions among Generation Z in Bandung City. A quantitative approach with an explanatory survey method was applied. Data were collected from 120 respondents aged 18–27 who actively use e-wallets and have investment experience. Multiple linear regression analysis was employed to examine the influence of each independent variable on investment decisions. The results reveal that financial literacy has a positive and significant effect on investment decisions, indicating that individuals with higher financial understanding tend to make more rational investment choices. Moreover, e-wallet usage positively influences investment decisions, implying that digital accessibility can foster greater participation of young people in investment activities. These findings highlight the importance of enhancing financial literacy among digital generations and developing e-wallet features that promote productive financial behavior.